2017
DOI: 10.26480/wcm.02.2017.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Blooms of Toxic Cyanobacteria in Freshwater in Algeria

Abstract: When water temperature and irradiance as well as meteorological conditions and nutrient supply are favourable, cyanobacteria can flourish in lakes and rivers where they can produce blooms usually in summer to late autumn, in both subtropical and temperate latitudes. Several of which are toxic and produce specifically hepatotoxins type microcyst ins. Studies undertaken in dams and natural lakes, particularly in the lake Oubeira and the dam Cheffia (East-Algeria), showed that these media evolve quickly to eutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Due to the flexibility of such tools, several land-use scenarios can be quickly evaluated, assessed, and compared. Even though this study only considered simple land-use change scenarios such as percentage increase in urban area, the effect of such land-use change is quickly apparent [32,33]. Moreover, more detailed examination of the impact and effects on each hydrological component can be performed.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the flexibility of such tools, several land-use scenarios can be quickly evaluated, assessed, and compared. Even though this study only considered simple land-use change scenarios such as percentage increase in urban area, the effect of such land-use change is quickly apparent [32,33]. Moreover, more detailed examination of the impact and effects on each hydrological component can be performed.…”
Section: Resultsmentioning
confidence: 99%
“…On the African continent, the environmental conditions are very conducive to continued proliferation of potentially toxic cyanobacteria (Ndlela et al 2016). For example in the North African basin, in Egypt (Mohamed 2016), in Morocco (Oudra et al 2001;Ouhsassi et al 2021), in Algeria (Nasri et al 2007;Nasri and Bouaïcha 2017) and in Tunisia (El Herry et al 2008;Fathalli et al 2015) blooms of cyanobacteria have been observed in several fresh surface waters during the warmer months, particularly in summer and early fall. Some arid West African countries such as Mauritania have made signi cant efforts to mobilize surface water resources through the construction of dams.…”
Section: Introductionmentioning
confidence: 99%
“…On the African continent, the environmental conditions are very conducive to continued proliferation of potentially toxic cyanobacteria (Ndlela et al 2016). For example in the North African basin, in Egypt (Mohamed 2016), in Morocco (Oudra et al 2001;Ouhsassi et al 2021), in Algeria (Nasri et al 2007;Nasri and Bouaïcha 2017) and in Tunisia (El Herry et al 2008;Fathalli et al 2015) blooms of cyanobacteria have been observed in several fresh surface waters during the warmer months, particularly in summer and early fall. Some arid West African countries such as Mauritania have made signi cant efforts to mobilize surface water resources through the construction of dams.…”
Section: Introductionmentioning
confidence: 99%